2022
DOI: 10.1039/d2cp03532d
|View full text |Cite
|
Sign up to set email alerts
|

CB6Al0/+: Planar hexacoordinate boron (phB) in the global minimum structure

Abstract: Herein, we report for the first time the presence of a planar hexacoordinate boron (phB) atom in the global minimum energy structure of a neutral cluster system. The potential energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…39 In another work, we showed that the PESs of CB 6 Al 0/+ clusters have a planar hexacoordinate boron (phB) in the GM structures (Figure 10d). 40 Moreover, the presence of a planar tetracoordinate boron (ptB) in the GM structures of BSi n Ge 4−n + (n = 0−2) clusters (Figure 10e−g) was also reported by us. 41 Other clusters with exotic properties, for example, the reactivity of small boron clusters, 42 their cooperativity, helical-shape spin densities, 43 helical molecular orbitals of conjugated linear molecules, 44 molecular electrides, 45,46 alkalides, 47,48 frustrated Lewis pairs (FLPs), 49,50 hypercoordinated carbon 51,52 and boron clusters, 53 fluxional molecules, 54−56 magic clusters, 57,58 etc., are some of the very interesting molecular groups that can be studied in the line of soft computing.…”
Section: Determination Of Global Minimum Energy Structures Of Hyperco...supporting
confidence: 69%
See 1 more Smart Citation
“…39 In another work, we showed that the PESs of CB 6 Al 0/+ clusters have a planar hexacoordinate boron (phB) in the GM structures (Figure 10d). 40 Moreover, the presence of a planar tetracoordinate boron (ptB) in the GM structures of BSi n Ge 4−n + (n = 0−2) clusters (Figure 10e−g) was also reported by us. 41 Other clusters with exotic properties, for example, the reactivity of small boron clusters, 42 their cooperativity, helical-shape spin densities, 43 helical molecular orbitals of conjugated linear molecules, 44 molecular electrides, 45,46 alkalides, 47,48 frustrated Lewis pairs (FLPs), 49,50 hypercoordinated carbon 51,52 and boron clusters, 53 fluxional molecules, 54−56 magic clusters, 57,58 etc., are some of the very interesting molecular groups that can be studied in the line of soft computing.…”
Section: Determination Of Global Minimum Energy Structures Of Hyperco...supporting
confidence: 69%
“…We explored the PES of CSi n Ge 4– n 2+/+/0 ( n = 1–3) clusters and found that the global minimum structures in the dicationic states contain a planar tetracoordinate carbon (ptC) (Figure a–c) . In another work, we showed that the PESs of CB 6 Al 0/+ clusters have a planar hexacoordinate boron (phB) in the GM structures (Figure d) . Moreover, the presence of a planar tetracoordinate boron (ptB) in the GM structures of BSi n Ge 4– n + ( n = 0–2) clusters (Figure e–g) was also reported by us .…”
Section: Soft Computing With Problem Solvingmentioning
confidence: 99%
“…Extensive theoretical research has been conducted to discover ptC atoms, , and recent studies have led to their experimental confirmation. , The current research focus is on other atoms that exhibit unconventional chemical bonding, resulting in planar structures. Several such atoms have been proposed, including planar hexacoordinated Ga, planar hexacoordinate B, planar pentacoordinate Zn, planar pentacoordinate Be, and planar tetracoordinate N . Theoretical investigations are ongoing in an effort to identify chemical species containing planar multiply coordinated atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [78][79][80][81][82], we have shown that it is a compelling technique for the analysis of aromaticity. Here also, we have employed the GIMIC method to calculate the ring current across various bonds at the TS structures of all four reactions (Table 5, Figure 8).…”
Section: Analysis Of Transition State Aromaticitymentioning
confidence: 99%